2002
DOI: 10.1034/j.1399-3054.2002.1140408.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased anthocyanin accumulation in aster flowers at elevated temperatures due to magnesium treatment

Abstract: Temperature is one of the main external factors affecting anthocyanin accumulation in plant tissues: low temperatures cause an increase and elevated temperatures cause a decrease in anthocyanin concentration. Several metals have been shown to increase the half-life time of anthocyanins, by forming complexes with them. We studied the combined effect of elevated temperatures and increased metal concentrations on the accumulation of anthocyanins in aster 'Sungal' flowers. It has been found that magnesium treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(62 citation statements)
references
References 27 publications
5
54
1
2
Order By: Relevance
“…Anthocyanin in many plants decreases as the temperature increases 10) due to the reduced activity of phenylalanine ammonia lyase. 11) A similar mechanism might operate to decrease the endogenous amount of aromatic scent compounds in P. axillaris flowers. The temperature-dependent modification of the scent composition ratio suggests that the multiple-branched metabolic network leading to each floral scent was differentially influenced by temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin in many plants decreases as the temperature increases 10) due to the reduced activity of phenylalanine ammonia lyase. 11) A similar mechanism might operate to decrease the endogenous amount of aromatic scent compounds in P. axillaris flowers. The temperature-dependent modification of the scent composition ratio suggests that the multiple-branched metabolic network leading to each floral scent was differentially influenced by temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that the degradation of anthocyanins is reduced due to Mg supply (Shaked-Sachray et al 2002), and more recently the same group provided evidence that Mg appears not to increase the biosynthesis, but rather to decrease the catabolism of anthocyanins in grape using cell suspension cultures (Sinilal et al Kristek (2000;, Gutmanski et al (1998) Oil palm Fruits, vegetables and ornamentals Apple N, P, K, Ca, Mg (salts or fertilizer not specified) soil 0 (no effect on juice pH), 0 (no effect on soluble solids and dry matter), 0 (no effect on titratable acidity) Dris et al 1999 Table 2 Tomato Ca, Mg (salts not specified fertigation (rockwool) + (increased firmness, texture) Hao and Papadopoulos (2004) Tomato K, Mg (salt not specified) soil 0 (no effect on juice pH and titratable acidity) Hara and Sonoda (1981) 2011). It would be interesting whether this phenomenon also occurs in important other crops and how this phenomenon operates at the molecular level.…”
Section: Fruitsmentioning
confidence: 99%
“…Magnesium increased the accumulation of anthocyanin in aster plants (Shaked-Sachray, Weiss, Reuveni, Nissim-Levi, & Oren-Shamir, 2002), increased the concentration of anthocyanin in Anthurium andraeanum flowers (Chen, Zhang, & Liang, 2010), and increased the accumulation of anthocyanin in red grape cell suspension cultures (Sinilal et al, 2011). In the present study, Mg fruit had higher h values than control fruit for much of the fruit development; there was no significant change in h values in response to Mg 17 days after treatment, indicating that the colour was saturated.…”
Section: Discussionmentioning
confidence: 96%